Effectiveness of Acupuncture Treatment on Chemotherapy-Induced Peripheral Neuropathy: A Pilot, Randomized, Assessor-Blinded, Controlled Trial. (29th June 2020) - Iravani, Somayeh; Kazemi Motlagh, Amir Hooman; Emami Razavi, Seyede Zahra; Shahi, Farhad; Wang, Jing; Hou, Li; Sun, Wenjun; Afshari Fard, Mohammad Reza; Aghili, Mahdi; Karimi, Mehrdad; Rezaeizadeh, Hossein; Zhao, Baixiao
Abstract : Objective . This pilot study aims to evaluate the effectiveness and safety of acupuncture in the treatment of chemotherapy-induced peripheral neuropathy (CIPN). Methods . This study was a pilot randomized controlled trial, which was conducted with cooperation between Beijing University of Chinese Medicine (BUCM), China, and Tehran University of Medical Science (TUMS), Iran. Forty participants with CIPN were randomly assigned (1 : 1) to receive twelve sessions of acupuncture (20 minutes each session over 4 weeks) or take one 300 mg tablet of vitamin B1 and three 300 mg capsules of gabapentin per day for 4 weeks, after which both groups were followed up for 4 weeks. The primary endpoint was CIPN symptom severity measured by the Numerical Rating Scale (NRS). The secondary endpoints included sensory neuropathy grade evaluated by the National Cancer Institute-Common Toxicity Criteria for Adverse Events (NCI-CTCAE), neurophysiological assessment of CIPN by the nerve conduction study (NCS), and the patient overall satisfaction with treatment. Safety was assessed at each visit. Results . The NRS and NCI-CTCAE sensory neuropathy grading scales decreased significantly over time in both groups (both P < 0.001 ), with a significantly higher reduction in the acupuncture group (P < 0.001 and P = 0.03, respectively). In addition, the acupuncture group showed a higher overall satisfaction with the treatment at the end of treatment and after 4 weeks follow-up, in comparison with the vit B1 and gabapentin group (P = 0.01 and P = 0.001, respectively). The NCS (except for the latency of the sural nerve) in the acupuncture group improved significantly (P < 0.05 ), while improvement in the vit B1 and gabapentin group was not observed (P > 0.05 ). Conclusion . Our study revealed that acupuncture, as a kind of traditional Chinese therapeutic method, is significantly effective and safe in the treatment of CIPN. Moreover, acupuncture is more effective than using vitamin B1 and gabapentin as the conventional treatment. Trial registration. This trial is registered with the Iranian Registry of Clinical Trials (IRCT20190615043900N1 ).